Answer:
x < 4
Step-by-step explanation:
We have that: 1 + 2x < 9. Let's solve this as if the < sign was an = sign:
1 + 2x < 9
Isolate the variable:
2x < 9 - 1
2x < 8
Divide by 2:
x < 8/2
x < 4
The answer is x < 4.
Answer: The common ratio is -1/3
-----------------------------------------------------------
Work Shown:
Pick any term to divide it by the previous term. I'm going to pick the second term and divide it by the first term.
r = common ratio
r = (term 2) divided by (term 1)
r = (4/9) divided by (-4/3)
r = (4/9) * (-3/4)
r = (4*(-3))/(9*4)
r = -12/36
r = -1/3
The common ratio is -1/3
This means you multiply each term by -1/3 to get the next term
For instance
term 2 = r*(term 1)
term 2 = (-1/3)*(-4/3)
term 2 = ((-1)*(-4))/(3*3)
term 2 = 4/9
Answer:
-12
Step-by-step explanation:
Answer:
1.25
Step-by-step explanation:
The bag of chips is worth the same as the entire purchase minus the soda.
Therefore the chips are worth 3 - 1.75 = 1.25